Advances in cryptology--EUROCRYPT 2017 : 36th Annual International Conference on the Theory and Applications of Cryptographic Techniques, Paris, France, April 30-May 4, 2017, proceedings /: 36th Annual International Conference on the Theory and Applications of Cryptographic Techniques, Paris, France, April 30-May 4, 2017, proceedings. ([2017]) - Unknown
No abstract available